2011
DOI: 10.1111/j.1559-1816.2011.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Women Assimilate Across Gender, Men Don't: The Role of Gender to the Own-Anchor Effect in Age, Height, and Weight Estimates1

Abstract: This paper reports 2 studies of the own‐anchor effect (i.e., assimilation in age, height, and weight estimates) in same‐ and cross‐gender age, height, and weight estimates. The own‐anchor effect is believed to be stronger for same‐gender estimates, but the investigation reported here is the first to test this hypothesis with participants and target persons of both genders. Several own‐anchor effects were found in females' same‐ and cross‐gender estimates, whereas males only showed own‐anchor effects in same‐ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 20 publications
2
23
0
1
Order By: Relevance
“…However, this result was not replicated in Experiment 2, making interpretations speculative. To our knowledge, there are only a few reports of an own‐anchor effect in age estimates (Ebbesen & Rienick, 1998; Sörqvist et al , 2008) and the results from these few studies are discrepant. Taken together, the own‐anchor effect in age estimates does not seem to be a robust general phenomenon.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, this result was not replicated in Experiment 2, making interpretations speculative. To our knowledge, there are only a few reports of an own‐anchor effect in age estimates (Ebbesen & Rienick, 1998; Sörqvist et al , 2008) and the results from these few studies are discrepant. Taken together, the own‐anchor effect in age estimates does not seem to be a robust general phenomenon.…”
Section: Discussionmentioning
confidence: 90%
“…This overestimation bias seems to be particularly pronounced for older people (George & Hole, 1995), perhaps reflecting a tendency to assimilate age estimates with one's own age. Such a tendency towards assimilation is labeled the own‐anchor effect and has been observed in several paradigms and across judgmental dimensions (Ebbesen & Rienick, 1998; Flin & Shepherd, 1986; Sörqvist, Langeborg & Eriksson, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…Mintz () found that children's estimates of Peter Pan's age correlated with their own age. The relationship has also been found in adults estimating the age of facial pictures (Vestlund, Langeborg, Sörqvist & Eriksson, ; Voelkle, Ebner, Lindenberger & Riediger, ) and of individuals they just met (Sörqvist, Langeborg & Eriksson, ). This assimilation of estimates of others toward one's own value has also been documented for height and weight estimates of pictured and actual persons (Flin & Shepherd, ; Sörqvist et al, ).…”
Section: Egocentricity In Comparison: a Brief Reviewmentioning
confidence: 73%
“…The relationship has also been found in adults estimating the age of facial pictures (Vestlund, Langeborg, Sörqvist & Eriksson, ; Voelkle, Ebner, Lindenberger & Riediger, ) and of individuals they just met (Sörqvist, Langeborg & Eriksson, ). This assimilation of estimates of others toward one's own value has also been documented for height and weight estimates of pictured and actual persons (Flin & Shepherd, ; Sörqvist et al, ). It occurs regardless of whether the judgments are made on an objective scale (years, inches, pounds) or on a subjective rating scale (Rethlingshafer & Hinckley, ).…”
Section: Egocentricity In Comparison: a Brief Reviewmentioning
confidence: 73%
See 1 more Smart Citation